Investigating the Effect of Sudden Stratospheric Warming on the Ionosphere above Basrah City - Al-Ubaidi, Najat M. R.; Hazim, Hawraa (Iraqi Journal of Physics, 2025)
The sudden thermal warming phenomenon in the stratosphere (SSW) occurred during wintertime, an important thing affecting communication throughout the ionosphere region. This study looks at how the SSW through the stratosphere temperature peak affects the three ionosphere parameters: the total electron content (TEC), the critical frequency foE, and the foF2 of two layers, E and F2. It uses the IRI-20 model over Basrah city, which is in the south of Iraq and lies at 30.4°N 47.7°E. This study spans 2014 and 2019, during the 24th solar cycle. In the same years, 10 hPa pressure heights are taken for hourly stratosphere temperature. It was found that there are (7) SSW events during the period selected, three in 2014 and four in 2019. The relation between stratospheric temperatures and ionospheric parameters was studied to find this effect. The results revealed non-linear relations between them during all event hours, but there is an increase in ionization. The TEC variation is remarkably present in all events, with positive ionization enhancement during the daytime, reaching a maximum in the afternoon and then going down after the sun sets. The foE and foF2 measurements also show a small change due to changes in the thermosphere’s make-up, temperature, winds, and either the F region dynamo or the E region dynamo. These changes also have an impact on the TEC enhancement values. This increment in values for the ionospheric parameters is irregular with time and varies from one parameter to another.